2015
DOI: 10.1016/j.amjcard.2015.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Outcome of Alcohol Septal Ablation With Confirmation by Nitroglycerin Test for Drug-Refractory Hypertrophic Obstructive Cardiomyopathy With Labile Left Ventricular Outflow Obstruction

Abstract: Careful evaluation, including provocation tests, is needed to specify an indication for septal reduction therapy in patients with drug-refractory hypertrophic obstructive cardiomyopathy. This study aimed to evaluate the outcome of alcohol septal ablation (ASA) using an intravenous nitroglycerin test (IV-NTG). Of consecutive 156 patients, after excluding cases of severe valvular disease and repeat septal reduction therapy, we investigated the clinical characteristics of patients with labile obstruction (n = 32)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Currently, indication for ASA is fundamentally determined by the degree of pressure gradient and assessment of life-limiting symptoms, assessed by NYHA grade [ 30 , 31 ]. However, a discrepancy between these two factors is frequently observed [ 17 ]. We therefore postulate that the severity and extent of 18 F-FDG uptake may be helpful for determining the indication for ASA, although further study is necessary to confirm the generalizability of our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, indication for ASA is fundamentally determined by the degree of pressure gradient and assessment of life-limiting symptoms, assessed by NYHA grade [ 30 , 31 ]. However, a discrepancy between these two factors is frequently observed [ 17 ]. We therefore postulate that the severity and extent of 18 F-FDG uptake may be helpful for determining the indication for ASA, although further study is necessary to confirm the generalizability of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Indication for HOCM was determined according to the following criteria: 1) symptoms were life limiting after optimization of medication, 2) resting or provoked gradient > 50 mmHg that was confirmed by at least one method during simultaneous pressure recordings, and 3) appropriate target branch(es) leading to the septal myocardium were responsible for intra-LV obstruction. ASA was performed as previously described [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Pressure gradient (PG) was calculated as the peak-to-peak difference of pressures between the ascending aorta and LV apex using a retrograde approach. Her intra-LVPG at rest was 10 mm Hg; however, a provocation test revealed that PG was 54 mm Hg using the Valsalva manoeuvre, 64 mm Hg using intravenous nitroglycerin (IV-NTG) and 136 mm Hg using both Valsalva manoeuvre and IV-NTG 8. We determined that her current drug-refractory symptoms were closely associated with LVOTO, an indication of septal reduction therapy.…”
Section: Case Presentationmentioning
confidence: 97%
“…These various clinical presentations are closely associated with narrowing LV capacity, intra-LV obstruction, severe tissue degradation, extensive myocardial fibrosis and diastolic dysfunction. Alcohol septal ablation (ASA) has been performed to treat hypertrophic obstructive cardiomyopathy (HOCM) when symptoms cannot be treated effectively even after optimisation of medical treatment 6–8…”
Section: Introductionmentioning
confidence: 99%
“…Peri-intervention monitoring of labile LVOT gradient is very practical. The intravenous nitroglycerin test during ASA is a useful method for rapidly confirming acute reduction of the latent gradient after the ASA procedure, and the outcome of ASA for labile obstruction was favorable [ 64 ].…”
Section: From Technical Point Of View In Both Surgical and Asa Promentioning
confidence: 99%